Rivaroxaban does not influence hemorrhagic transformation in a diabetes ischemic stroke and endovascular thrombectomy model - Feng-Di Liu (Nature Portfolio, 2018)
Abstract Managing endovascular thrombectomy (ET) in diabetic ischemic stroke (IS) with novel anticoagulants is challenging due to putative risk of intracerebral hemorrhage. The study evaluates increased hemorrhagic transformation (HT) risk in Rivaroxaban-treated diabetic rats post ET. Diabetes was induced in male Sprague-Dawley rats by intraperitoneal injection of 60 mg/kg streptozotocin. After 4-weeks, rats were pretreated orally with 30 mg/kg Rivaroxaban/saline; prothrombin time was monitored. IS and ET was induced after 1 h, by thread-induced transient middle cerebral artery occlusion (tMCAO) that mimicked mechanical ET for proximal MCA occlusion at 60 min. After 24 h reperfusion, infarct volumes, HT, blood-brain barrier (BBB) permeability, tight junction at peri-ischemic lesion and matrix metalloproteinase-9 (MMP-9) activity was measured. Diabetic rats seemed to exhibit increased infarct volume and HT at 24 h after ET than normal rats. Infarct volumes and functional outcomes did not differ between Rivaroxaban and diabetic control groups. A significant increase in HT volumes and BBB permeability under Rivaroxaban treatment was not detected. Compared to diabetic control group, neither the occludin expression was remarkably lower in the Rivaroxaban group nor the MMP-9 activity was higher. Together, Rivaroxaban does not increase HT after ET in diabetic rats with proximal MCA occlusion, since Rivaroxaban has fewer effects on post-ischemic BBB permeability.